"Layer peeling" co-delivery system for enhanced RNA interference-based tumor associated macrophages-specific chemoimmunotherapy. Issue 32 (6th August 2020) - Wang, Tianqi; Mu, Weiwei; Li, Feifei; Zhang, Jing; Hou, Teng; Pang, Xiuping; Yin, Xiaolan; Zhang, Na
Abstract : "Layer peeling" co-delivery systems provide a novel strategy to realize xenotype cells-targeting delivery and enhance the cancer chemoimmunotherapy effects. Abstract : RNA interference (RNAi)-based immunotherapy combined with chemotherapy has emerged as a promising therapeutic strategy for cancer treatment. The transport of siRNA and small molecular agents from the tumor vasculature to a separate therapeutic target has been impeded by multiple physiological barriers, which has restricted the development of RNAi-based chemoimmunotherapy. A nanotechnology-based co-delivery system was superior in improving the co-localization of gene and drug in the same tumor cell, while a co-delivery system for chemoimmunotherapy was expected to realize xenotype cell-targeting, which means delivering immunotherapy agents and chemotherapy drugs to immune cells and tumor cells, respectively. A multilayer structure co-delivery system was outstanding in crossing these barriers and targeting different cells in tumor tissue. Herein, a "layer peeling" co-delivery system (CDMPR) was developed with co-loaded IKKβ-siRNA and doxorubicin (DOX), in which IKKβ-siRNA was used for RNAi-based tumor associated macrophages (TAMs) polarization for immunotherapy and DOX was used for chemotherapy. A transwell assay in vitro and an immunofluorescence assay in Hepa1–6 tumor-bearing mice indicated that CDMPR exhibited a pH-sensitive disassembly ability in tumor tissue, IKKβ-siRNA was precisely delivered to M2-type TAMs and DOX was internalized into tumor cells. An M2-type TAMs polarization ability study of CDMPR demonstrated that M2-type TAMs could be polarized to M1-type TAMs by CDMPR in vitro and in vivo . In Hepa1–6 tumor-bearing mice, CDMPR exhibited improved antitumor efficiency with M2-type re-polarization ability by the precise delivery of IKKβ-siRNA and DOX to M2-type TAMs and tumor cells, respectively. Consequently, the combination of RNAi-based TAMs polarization and chemotherapy by the "layer peeling" co-delivery system would achieve an enhanced chemoimmunotherapy effect, which provides a novel strategy to improve cancer therapeutic effects.